Does conditionality in IMF-supported programs promote revenue reform? - Crivelli, Ernesto (IMF Working Papers; Working Paper ;, 2014)
This paper studies whether revenue conditionality in Fund-supported programs had any impact on the revenue performance of 126 low- and middle-income countries during 1993-2013. The results indicate that such conditionality had a positive impact on tax revenue, with strongest improvement felt on taxes on goods and services, including the VAT. Revenue conditionality matters more for low-income countries, particularly those where revenue ratios are below the group average. Moreover, revenue conditionality appears to be more effective when targeted to a specific tax. These results hold after controlling for potential endogeneity, sample selection bias, and when revenues are adjusted for economic cycle.